Optimalisasi Tata Kelola PAMDes melalui Pendampingan Laporan Keuangan, Struktur Organisasi, dan Program Konsumen Teladan - Zahra, Haura; Fitriyanto, Muhammad Zaki 'Aaqila; Agnitami, Zhelda Shafira; Widyaningsih, Aristanti; Nurrizkiana, Rika (Universitas Muhammadiyah Mataram, 2025)
This assistance aims to optimize the governance of PAMDes Sauyunan, Cihideung Village, West Bandung Regency through assistance in financial reports, creating an organizational structure, and strengthening payment awareness through the exemplary consumer program. Participatory methods were observation and interviews. The activity stages were observation and interviews. The activity stages were identification, planning, and output delivery. The results showed an increase in staff participation in financial recording to 80%, clarity of roles through the organizational structure, and the expected growth of a culture of payment discipline. In addition to the impact on partners, this activity also improved students' soft and hard skill, especially in communication and designing financial reporting system.Pendampingan ini bertujuan mengoptimalkan tata kelola PAMDes Sauyunan Desa Cihideung Kabupaten Bandung Barat melalui pendampingan pada laporan keuangan, pembuatan struktur organisasi, dan penguatan kesadaran pembayaran melalui program konsumen teladan. Metode partisipatif adalah observasi dan wawancara. Tahapan kegiatan adalah identifikasi, perencanaan, dan penyerahan output. Hasilnya menunjukkan peningkatan partisipasi staf dalam pencatatan keuangan hingga 80%, kejelasan peran melalui struktur organisasi, serta diharapkan tumbuhnya budaya disiplin pembayaran. Selain berdampak pada mitra, kegiatan ini turut meningkatkan softskill dan hardskill mahasiswa, khususnya dalam komunikasi dan perancangan sistem pelaporan keuangan.